Adsorption–desorption behavior of methylene blue onto aged polyethylene microplastics in aqueous environments. (June 2021) - You, Huimin; Huang, Baoquan; Cao, Changlin; Liu, Xinping; Sun, Xiaoli; Xiao, Liren; Qiu, Jianbin; Luo, Yongjin; Qian, Qingrong; Chen, Qinghua
Abstract: In this study, polyethylene microplastics were artificially photoaged by xenon light. Experiments were then performed with methylene blue (MB) dye to compare the changes in the structure, properties, and adsorption–desorption behaviors of the aged and virgin polyethylene microplastics. The results showed that the aged polyethylene microplastics were hydrophilic with oxygen-containing functional groups, which enhanced the adsorption capacity of polyethylene for MB from 0.63 mg·g −1 to 8.12 mg·g −1 . The adsorption isotherms changed from the Henry model (virgin polyethylene microplastics) to the Langmuir model (aged polyethylene microplastics), indicating that the partitioning function was gradually replaced by a single-layer covering during the adsorption process. In addition, 7% and 17.8% of the MB loaded onto the aged polyethylene microplastics was desorbed into water and a simulated intestinal fluid, respectively. These findings reveal that aged polyethylene microplastics can accumulate MB, thus posing potential risks to aqueous environments and biological tissues. Highlights: The adsorption capacity of MB on aged polyethylene MPs is much greater than that of virgin microplasticMPs due to different adsorption mechanism for MB. 17.8% of loaded MB on the aged polyethylene microplastics can be desorbed in simulated intestinal fluid. Polyethylene MPs are substantial vectors for MB in the aquatic environment.